Essays on foreign direct investments and preferential trade agreements - Hiraide, Norikatsu (Kansas State University, 2021)
This dissertation consists of three essays. The first essay investigates the importance of preferential trade agreement (PTA) formation in attracting inflows of foreign direct investment (FDI). In particular, we examine the heterogeneous effects of different types of PTAs (FTAs or CUs) on the extensive and intensive margins of FDI and on how the interdependence among various PTAs may affect a country’s ability to attract FDI inflows. We find that the larger the preferential markets to which a country has access, the larger the FDI inflows the country receives. Furthermore, we find that the type of PTA matters in determining FDI inflows. In this case, we find that the formation of CUs tends to promote FDI inflows more than the formation of FTAs. Our findings also indicate that the formation of PTAs significantly affects FDI through the intensive margin rather than through the extensive margin. Importantly, notice that these effects are driven by the preferential markets to which a country has access and that have not established a PTA with the FDI-originating (home) country, confirming that PTA interdependence matters in determining FDI inflows. The second essay examines the effects of U.S. exposure to international trade in goods and services on U.S. local labor markets. The paper finds that the average increase in U.S. exposure to FDI inflows increases the share of manufacturing employment, while the average increase in U.S. exposure to FDI outflows reduces the share of manufacturing employment in the U.S. local labor markets. Overall, the average increase in U.S. exposure to international trade in goods and services is associated with a 0.049 percentage point increase in the share of manufacturing employment from 1991 to 2007. We quantify the employment impact and find that the implied employment changes due to U.S. exposure to international trade in goods and services are about 1.36 million over the period 1991-2007. The paper also investigates the employment and wage effects of U.S. exposure to international trade in goods and services and finds the positive net employment and wage effects from 1991 to 2007. The third essay investigates the effects of the formation of PTAs on different FDI strategies, including vertical, horizontal, and export-platform FDI. In addition, we examine heterogeneous effects of different types of PTAs (FTAs or CUs) on the intensive and extensive margins of each type of FDI and on how the interdependence among various PTAs may affect a host country’s ability to attract each type of FDI. We find that a host country enlarging preferential markets through the formation of PTAs with other economic partners promotes the U.S. multinationals’ horizontal and export-platform FDIs. On the other hand, a host country forming a PTA with the U.S. receives more vertical FDI. Also, we find that the formation of CUs tends to promote horizontal and export-platform FDI more than the formation of FTAs. Moreover, our results show that U.S. multinationals increase each type of FDI through the intensive margin of FDI.
Keywords: Preferential trade agreements; Foreign direct investments; Trade and labor market interactions; Market potential; Multinational firms